The persuasive leader : lessons from the arts - Carroll, Stephen J., 1930-; Flood, Patrick C. (San Francisco : Jossey-Bass, a Wiley imprint.c 2010., 2010)
"The communication aspect of leadership - to actively engage your followers and achieve understanding and motivation whilst making the message memorable - has never been more important. Using vivid lessons and examples from spheres outside business organizations, The Persuasive Leader explores the leader's role as a communicator and teaches the fundamental principles of successful leadership.
"This book provides insights and principles about persuasive leadership from a broad range of human experiences. It draws on examples of persuasive leaders and persuasive leadership principles from the performing arts, the fine arts, literature, philosophical writings, and biography. The authors use their unconventional material to explore themes such as moral leadership, toxic leadership, learning from failures, 'distributed' leadership, leading for results and the leader as a mentor and counsellor. --Publisher description.
Persuasive leadership in life and work -- Using aesthetics and the arts in persuasive leadership -- Using words effectively in persuasive speech and writing -- Persuasive leadership and rhetoric principles -- Persuasive leadership-planning considerations -- Audience characteristics -- Leader-follower emotional ties -- Creating positive responses in sub-leaders and followers -- Persuasive leadership and change -- Strategic plans as a persuasive tool -- Harmful persuasion -- Self-leadership -- Persuasive variations in different settings -- Achieving trust and cooperation -- The noble persuasive leader -- Leadership emergence -- Handling problems and failure -- Why become a persuasive leader?
Includes bibliographical references and index.
Keywords: Leadership; Persuasion (Psychology) in organizations; Communication in management; Leadership; Communication en gestion; Communication in management; Leadership; Persuasion (Psychology) in organizations